iBehavior—a preliminary proof of concept study of a smartphone-based tool for the assessment of behavior change in neurodevelopmental disabilities - Dakopolos, Andrew; Glassman, Dana; Scott, Haleigh; Bass, Michael; Hessl, David (Frontiers in Psychology, 2023)
Purpose The purpose of the present study was to describe the content and function of iBehavior, a smartphone-based caregiver-report electronic ecological momentary assessment (eEMA) tool developed to assess and track behavior change in people with intellectual and developmental disabilities (IDDs), and to examine its preliminary validity. Methods Ten parents of children (ages of 5–17 years) with IDDs (n = 7 with fragile X syndrome; n = 3 with Down syndrome) rated their child’s behavior (aggression and irritability, avoidant and fearful behavior, restricted and repetitive behavior and interests, and social initiation) using iBehavior once daily for 14 days. At the conclusion of the 14-day observation period, parents completed traditional rating scales as validation measures, as well as a user feedback survey. Results Across the 140 possible observations, 8 were skipped, leading to a 94% response rate over 10 participants’ observation periods. Participants also completed 100% of items for each of their logged observations. Parent ratings using iBehavior showed emerging evidence of convergent validity among domains with traditional rating scales including the Behavior Rating Inventory of Executive Function 2 (BRIEF-2), and Aberrant Behavior Checklist-Community (ABC-C). iBehavior was feasible in the sample, and parent feedback indicated high overall satisfaction. Conclusion Results of the present pilot study indicate successful implementation and preliminary feasibility and validity of an eEMA tool for use as a behavioral outcome measure in IDDs.